Flavonoid Compounds Contained in Epimedii Herba Inhibit Tumor Progression by Suppressing STAT3 Activation in the Tumor Microenvironment - Pan, Cheng; Fujiwara, Yukio; Horlad, Hasita; Shiraishi, Daisuke; Iriki, Toyohisa; Tsuboki, Jyunko; Ikeda, Tsuyoshi; Komohara, Yoshihiro (Frontiers in Pharmacology, 2020)
It is well known that the M2-like tumor-associated macrophages (TAMs) in tumor tissues promote tumor progression by various mechanisms and that these TAMs are possible targets for antitumor therapy. In the present study, using human monocyte-derived macrophages (HMDMs) and animal sarcoma models, we tested whether compounds from Epimedii Herba inhibit macrophage polarization into the M2/protumorigenic phenotype and prevent tumor progression. Four flavonoid compounds, namely, limonianin, epimedokoreanin B, icaritin, and desmethylicaritin, inhibited CD163 expression and IL-10 production, which are known to be M2 markers, thus suggesting that these compounds inhibit M2 polarization. Among these compounds, epimedokoreanin B and limonianin suppressed STAT3 activation in HMDMs. Notably, epimedokoreanin B also suppressed cell proliferation by blocking STAT3 activation in SaOS2 human sarcoma and LM8 mouse sarcoma cell lines. Furthermore, oral administration of epimedokoreanin B inhibited tumor growth in an LM8 tumor-bearing murine model. These results indicate that Epimedii Herba and Epimedii Herba-derived compounds, such as epimedokoreanin B, may be potentially new agents that can be used for the treatment and prevention of various malignant tumors by inhibiting the M2 polarization of TAMs.